ort each equation according to whether it has one solution, infinitely many solutions, or no solution

-3(X - 4) = – 3x + 12
4(x + 1) = 3x + 4
-2(x-3) = 2x - 6
6(x + 5) = 6x + 11
5(x-2)=5x-7

Respuesta :

The first one is infinite many solutions
The second one is (x=0) one solution
The third one is (x=3) one solution
The fourth one is no solution
The last one is no solution

-3(X - 4) = – 3x + 12 infinite solutions

4(x + 1) = 3x + 4 one solution

-2(x-3) = 2x - 6 one solution

6(x + 5) = 6x + 11 no solution

5(x-2)=5x-7 no solution

ACCESS MORE